2004
DOI: 10.1007/s00424-003-1205-x
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated Na + channels confer invasive properties on human prostate cancer cells

Abstract: Prostate cancer is the second leading cause of cancer deaths in American males, resulting in an estimated 37,000 deaths annually, typically the result of metastatic disease. A consequence of the unsuccessful androgen ablation therapy used initially to treat metastatic disease is the emergence of androgen-insensitive prostate cancer, for which there is currently no prescribed therapy. Here, three related human prostate cancer cell lines that serve as a model for this dominant form of prostate cancer metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 28 publications
(30 reference statements)
5
81
0
1
Order By: Relevance
“…In addition, 200 nM TTX did not demonstrate toxicity against the two cell lines. Metastatic properties of Mat-LyLu and AT-2 cells are closely associated with VGSCs, as has been demonstrated in studies on TTX, which specifically blocks VGSCs (4,7,8,11). In the present study, 200 nM TTX was used as the positive control, as it has been previously reported that TTX does not produce changes in the proliferation of either cell line even at higher doses (600 nM and 6 µM) than 200 nM (5,7,27).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…In addition, 200 nM TTX did not demonstrate toxicity against the two cell lines. Metastatic properties of Mat-LyLu and AT-2 cells are closely associated with VGSCs, as has been demonstrated in studies on TTX, which specifically blocks VGSCs (4,7,8,11). In the present study, 200 nM TTX was used as the positive control, as it has been previously reported that TTX does not produce changes in the proliferation of either cell line even at higher doses (600 nM and 6 µM) than 200 nM (5,7,27).…”
Section: Resultssupporting
confidence: 54%
“…Ion channels regulate, and stimulate numerous behavioral changes in cells that are associated with cancer and metastasis, including cell movement (elongation and lateral motility) (4,5), migration, galvanotaxis (6) and invasion (7,8). A number of in vitro (9)(10)(11) and in vivo (12) studies performed using tetrodotoxin (TTX), which specifically blocks voltage-gated sodium channels (VGSCs) (13), have suggested that the plasma membrane of prostate cancer cells may gain a more excitable phenotype due to increased VGSC expression, and thus malignancy is able to progress. Bennett et al (11) demonstrated that VGSC expression was 'necessary' and 'enough' for the invasiveness of prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain why there is no need for a large increase in b1-expression (concomitant with the large increase in VGSCa-expression) in strongly metastatic CaP cells, and would also be consistent with overexpression of VGSCa alone in LNCaP cells being sufficient to increase significantly their in vitro invasiveness. 43 Despite the absence of a large increase in VGSCbexpression, these subunits might still have an important role in VGSC functioning in CaP, and thus in VGSCmediated potentiation of metastatic cell behaviours. Indeed, reducing b1-expression or perturbing its association with Na v 1.7 could alter key channel properties such as activation/inactivation and recovery from fast inactivation that would result in less VGSC activity and inhibition of VGSC-potentiated metastatic cell behaviour.…”
Section: Vgsca and Vgscb Interactions In Cap Cellsmentioning
confidence: 99%
“…Metastasis is a process where cells escape from a primary tumor, enter circulation (blood or lymph), migrate and invade other tissues, proliferate and form secondary tumors. In in vitro experiments, it has been shown that VGSCs are associated to proliferation, motility, and invasion of breast, lung, ovary and prostate cancer (Roger et al, 2003;Gao et al, 2010;Diss et al 2005;Chioni et al, 2010;Roger et al, 2007;House, et al, 2010;Bennett et al, 2004). In prostate cancer cells, the main VGSC overexpressed is the Na V 1.7 subunit, while in breast, colon and ovary the Na V 1.5 subunit is the predominant subunit overexpressed.…”
Section: Sodium Channelsmentioning
confidence: 99%